2009
DOI: 10.1124/jpet.109.158022
|View full text |Cite
|
Sign up to set email alerts
|

Mesalamine Restores Angiogenic Balance in Experimental Ulcerative Colitis by Reducing Expression of Endostatin and Angiostatin: Novel Molecular Mechanism for Therapeutic Action of Mesalamine

Abstract: Mesalamine (5-aminosalicylate acid, 5-ASA) is an effective treatment for ulcerative colitis (UC). The mechanisms of its actions are not fully understood. Because angiogenesis is critical for healing UC, we examined whether 5-ASA alters the angiogenic balance between angiogenic factors [e.g., vascular endothelial growth factor (VEGF)] and antiangiogenic factors (e.g., endostatin and angiostatin) in the colon in experimental UC. Rats were treated with saline or 5-ASA (100 mg/kg) twice daily and euthanized 3 or 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…In this study we demonstrated a concurrent increase of angiogenic VEGF and anti-angiogenic endostatin and angiostatin in the duodenal mucosa during chemically induced duodenal ulceration, indicating, for the first time, an altered balance between pro-and anti-angiogenic factors in duodenal ulceration. We also detected a similar interaction between angiogenic and anti-angiogenic factors in rats with experimental ulcerative colitis [27,28]. These unexpected findings may actually explain, for the first time, the initially surprising results demonstrating increased levels of angiogenic growth factors (e.g., bFGF, PDGF, VEGF) in the early stages of experimental duodenal ulceration.…”
Section: Discussionsupporting
confidence: 51%
“…In this study we demonstrated a concurrent increase of angiogenic VEGF and anti-angiogenic endostatin and angiostatin in the duodenal mucosa during chemically induced duodenal ulceration, indicating, for the first time, an altered balance between pro-and anti-angiogenic factors in duodenal ulceration. We also detected a similar interaction between angiogenic and anti-angiogenic factors in rats with experimental ulcerative colitis [27,28]. These unexpected findings may actually explain, for the first time, the initially surprising results demonstrating increased levels of angiogenic growth factors (e.g., bFGF, PDGF, VEGF) in the early stages of experimental duodenal ulceration.…”
Section: Discussionsupporting
confidence: 51%
“…Proteins were extracted using lysis buffer and analyzed by Western blots (9). Lysates (100 g) were separated (15% SDS-PAGE) and blotted to polyvinylidene difluoride.…”
Section: Methodsmentioning
confidence: 99%
“…On day 0, rats were weighed, given respective treatments of either sulfasalazine (100 mg/kg in olive oil p.o.) (Deng et al, 2009), GB88 (10 mg/kg in olive oil), or vehicle (500 l olive oil p.o. ), and fasted for 24 h with water supplied ad libitum.…”
Section: Methodsmentioning
confidence: 99%